جام درک،مست توکلی، ملافاضل ءِ شاعری ءِ درشاندابی دیم پہ دیمی وانشت: Comparative study of diction in poetry of Jam Duruk,Masth Thokali and Mullah Fazul - ullah, Nehmat; Baloch, Hamid Ali (Hanken, 2018)
This paper demonstrates a comparative study of the poetical works of contemporary poets’ e.g Jám Durrak, Mulla Fázil and Tawkali Mast. The main themes covered in this paper are comparative study of mysticism, creativity, resemblance and similarities, and lexical structure of the verses. The way of expression, description of landscapes and sceneries, the description of faces and countenance of beautiful ladies. The fine structures and figures of lovers. Occasionally, there is a huge resemblance in of the poetry of three great poets. The religious aspects in poetry of Mullah Fazil is somehow huge, while the poetry of Jam Durrak and Tawkali is based on romanticism